Oral nanoparticles based on gellan gum/pectin for colon-targeted delivery of resveratrol - Prezotti, Fabíola Garavello [UNESP]; Boni, Fernanda Isadora [UNESP]; Ferreira, Natália Noronha [UNESP]; Silva, Daniella Souza; Almeida, Andreia; Vasconcelos, Teófilo; Sarmento, Bruno; Gremião, Maria Palmira Daflon [UNESP]; Cury, Beatriz Stringhetti Ferreira [UNESP] (Taylor & Francis, 2020)
Nanoparticles based on gellan gum/pectin blends were designed for colon-targeted release of resveratrol (RES). Their impact on drug release rates and permeability were evaluated using Caco-2 cell model and mucus secreting triple co-culture model. Polymeric nanoparticles (PNP) were successfully prepared by nebulization/ionotropic gelation, achieving high drug loading (>80%). PNP were spherical with a low positive charge density (+5mV) and exhibited diameters of around 330 nm. Developed PNP were able to promote effective modulation of drug release rates, so that only 3% of RES was released in acidic media over 2 h, and, in pH 6.8, the drug was released in a sustained manner, reaching 85% in 30 h. The permeability of RES-loaded PNP in the Caco-2 model was 0.15%, while in the triple co-culture model, in the presence of mucus, it reached 5.5%. The everted gut sac experiment corroborated the low permeability of RES-loaded PNP in the presence or absence of mucus and highlighted their high ability to interact with the intestinal tissue. Results indicate that the novel PNP developed in this work are safe and promising carriers for controlled delivery of RES at the colon.
Keywords: caco-2 cells; colon-targeted release; everted gut sac; in vitro permeability; Polymeric nanoparticles; triple co-culture model